Kartu Ajaib Qur’ani: Media Pembelajaran Hewan dalam Al-Qur’an untuk Siswa Madrasah Ibtidaiyah : Studi Efektivitas terhadap Pemahaman dan Minat Belajar Siswa - Muhammad Zaki Mubarok; Zidan Muhammad Fadhil; Nur Fajriansyah; Faruq At Taqi; Ahmad Nurrohim (STIKes Ibnu Sina Ajibarang, 2026)
Learning the Qur'an in Islamic Elementary Schools requires an approach that emphasizes not only reading skills but also understanding the meaning and internalizing the Qur'anic values ​​contextually. However, learning practices that are still dominated by conventional methods have the potential to reduce student engagement and interest in learning, especially in narrative materials such as animal stories in the Qur'an. This study aims to examine the effectiveness of the Qur'anic Magic Cards media as a learning medium for animals in the Qur'an in increasing the understanding and interest in learning of students in Islamic Elementary Schools. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the use of the Qur'anic Magic Cards media can help students understand the meaning of verses more concretely, increase active involvement during learning, and foster interest in learning the Qur'anic material. This media also contributes to creating a fun, contextual, and meaningful learning atmosphere, so that the messages of the Qur'an are not only understood textually but also internalized in the learning process. Thus, the Magic Quran Cards can be used as an innovative and relevant alternative Quranic learning medium for implementation in Islamic Elementary Schools (Madrasah Ibtidaiyah).